(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2021)
The mass media play at least five basic functions which include news dissemination, surveillance of the environment, correlation of the components of the society, entertainment and transmission of social heritage. Sometimes, disruptions and impairments do occur in the performance of these roles and some of these basic functions become dysfunctions, which turn the media into purveyor of negative values. The present study investigates how popular the Nigerian TV reality show, Big Brother Naija (BBN), is perceived by its viewers. Three hundred heavy viewers of the programme were surveyed from Lagos and Ede, South-West Nigeria, and their opinions and attitudes were sought regarding; why they like or dislike the programme; the gratifications that those who like the programme derive and whether the BBN, as media content, is generally functional or dysfunctional to the society. Sixty-six per cent 66 (33.7%) of respondents like the programme because it entertains. Half of the respondents, 99(50.5%) dislike ‘immoral aspects’ of the programme. The viewers affirm that the eviction part of the programme was their highest form of gratification. Most respondents, despite public outcry against the programme, consider the programme to be “functional”. Findings reinforce the postulation that TV viewers are not passive consumers of media contents.